Students’ Perceptions on the TOEFL Test and Its Relevant Factors - Arnelli Arnelli (Educare: Journal Educational and Multimedia, 2025)
This study explores students’ perceptions of the TOEFL test and the relevant factors influencing their English proficiency. The TOEFL test has become a mandatory component in many Indonesian higher education institutions and is widely required in professional sectors. Using a qualitative approach, the research involved undergraduate students from a privately funded university who had completed a TOEFL course. Data were collected through written interviews to ensure authenticity and minimize researcher influence. The findings reveal that students acknowledge the importance of TOEFL for academic and employment opportunities. However, many perceive the official TOEFL test as financially burdensome and question its ability to fully reflect their English capabilities, particularly for those who acquired English informally. Students also emphasized the need for more practical language skills, such as oral communication, in addition to test preparation. The study concludes that English instruction should align with students’ future career needs while maintaining the validity of standardized assessment tools.